Quantitative determination of pravastatin and its metabolite 3α-hydroxy pravastatin in plasma and urine of pregnant patients by LC-MS/MS - Zhang, Xing (Biomed Chromatogr, 2015)
This report describes the development and validation of a chromatography/tandem mass spectrometry method for the quantitative determination of pravastatin and its metabolite (3α-hydroxy pravastatin) in plasma and urine of pregnant patients under treatment with pravastatin, as part of a clinical trial. The method includes a one-step sample preparation by liquid-liquid extraction. The extraction recovery of the analytes ranged between 93.8% and 99.5% in plasma. The lower limits of quantitation (LLOQ) of the analytes in plasma samples were 0.106 ng/mL for pravastatin and 0.105 ng/mL for 3α-hydroxy pravastatin; while in urine samples they were 19.7 ng/mL for pravastatin and 2.00 ng/mL for 3α-hydroxy pravastatin. The relative deviation of this method was < 10 % for intra-day and inter-day assays in plasma and urine samples, and the accuracy ranged between 97.2% and 106% in plasma, and 98.2% to 105% in urine. The method described in this report was successfully utilized for determining the pharmacokinetics (PK) of pravastatin in pregnant patients enrolled in a pilot clinical trial for prevention of preeclampsia.